PERILAKU MELANGGAR PERATURAN PADA SANTRI Dl PONDOK PESANTREN - Fx. Wahyu Widiantoro dan Romadhon (Jurnal Psikologi, 2015)
Breaking rules is more likely an important characteristic among adolescences. This is also occurred in a pesantren (Islamic boarding school). The adolescence santri broke the pesantren rules because of two factors, internal and external. The internal factors underlie the breaking rules behavior comprised three things i.e. low self-control, egocentrism, and aggressive. The external factor, on the other hand, influenced the adolescence santri through several reasons i.e. peer conformity, immoral behavior among the pesantren caretakers. Subject of this preliminary research is a male adolescence. He is chosen since he was reported to have several breaking rule behaviors. This qualitative research confirmed the theory on internal and external factors influencing the breaking rules behavior. Several limitation and suggestion for the preliminary research are discussed.